The role of lecturer discipline on student interests: motivation to learn as intervening variable - Man Yany; Djoko Soelistya; Eva Decembrianita; Rahmat Agus Samtoso; Mu’minatur Sholichah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The world of higher education is required to always update knowledge and skills. Lecturers as an important factor in improving the quality of education have an effect on student interest in learning and student interest in learning is needed for lecturer discipline. This study aims to analyze the effect of lecturer discipline owned by a lecturer in increasing student interest in learning through their learning motivation. This study uses a quantitative method with a population of college students majoring in management, which uses a sample of 99 respondents whose analysis uses the SmartPLS 3.0 program, and the results of this study show that the influence of (1) Lecturer Discipline has a significant direct effect on learning interest; (2) Lecturer discipline has a significant direct effect on learning motivation; (3) learning motivation has a significant direct effect on learning interest while (4) Lecturer discipline has a significant but not direct effect on learning interest,and seeing the results of the effect of mediation shows that Lecturer Discipline can increase Learning Interest directly even without going through Learning Motivation as a mediating variable which means that a lecturer really needs his teaching motivation by providing timely teaching and learning so that students feel comfortable with the lecturer's discipline in teaching to make students enthusiastic. learning increases.